The Performance of Some Durum Wheat (Triticumturgidum L.) Under Different Environmental Conditions of Sulaimani / Kurdistan Iraq. - Rasool, Abdulsalam A.; Rasheed, Mohamad A. Hama; Raza, Taha Y.; Rasheed, Zanko O.; Khider, Hiwa A. Hamad (Sulaimani Journal for Pure and Applied Sciences, 2013)
A field experiment was carried out during the winter season 2011-2012, to evaluate the performance of 8 new varieties of durum wheat (Triticum turgidum L.), namely (V1: Amidacul, V2: Bejah, V3: Guayacaninia Yuan-1/ Green-18, V4: Fadda, V5: Halio, V6: Omyavoros 79, V7: Simeto, and V8: Ovanto), under four different agro climatic conditions, namely BAKRAJO, KANI PANKA, GRDAJAN, and BAZYAN. Completely Randomized Block design (CRBD) with 3 replications were used in each location. The results shows that V7 required the shortest period for heading in all locations and their average with the exception of the 3rd location, when the V7 required the longest period for heading among the varieties. Regarding the plant height, the V4 shows a stable superiority in all locations without exception, while V8 significantly predominated in the 1000-grain weight compared to the other varieties in all locations and their average, but the maximum No. of grains spike-1 were fluctuated between the varieties within the locations. Maximum grain yield obtained by the V7 in the 1st , 2nd , 4th , and the average of locations were in accordance with the shortest period for heading of V7 at those locations, but the biological yield was different in superiority among varieties within locations. Finally the results of the agronomic characters in different locations indicated that the 2nd location was suit for early planting, which causing the reduction in heading period, and increasing the grain and biological yield as average of varieties, due to the maximum period for growth and development toward the maturity in this location.
Keywords: Durum wheat; Varieties; Rainfall; Soil condition; Heading; Grain yield